Peranan Community Based Approach Penyuluh Agama dalam Mengedukasi Dampak Pernikahan Dini pada Masyarakat Desa Pulau Harapan - Suryati Suryati; Selvia Selvia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of the community-based approach implemented by religious counselors in educating the public about the impacts of early marriage in Pulau Harapan Village. Early marriage remains a significant issue in this area, affecting health, education, and social welfare. Through a community-based approach, religious counselors strive to raise awareness by utilizing local social structures, religious perspectives, and active citizen participation in educational activities. This research uses a qualitative method with a case study approach, involving observation, in-depth interviews, and documentation. The findings indicate that religious counselors play a strategic role in delivering moral and educational messages aligned with local religious and cultural values. The application of the community-based approach has proven effective in increasing public understanding of the risks of early marriage and gradually encouraging attitudinal change. However, challenges remain, including limited resources and cultural resistance, which must be addressed collaboratively.